Impact of preoperative infection on outcome after liver transplantation. Issue 2 (25th January 2017) - Bertuzzo, V R; Giannella, M; Cucchetti, A; Pinna, A D; Grossi, A; Ravaioli, M; Del Gaudio, M; Cristini, F; Viale, P; Cescon, M
Abstract: Background: Bacterial infection in patients with liver failure can lead to a dramatic clinical deterioration. The indications for liver transplantation and outcome in these patients is still controversial. Methods: All adult patients who underwent liver transplantation between 1 January 2010 and 31 December 2015 were selected from an institutional database. Characteristics of the donors and recipients, and clinical, biochemical and surgical parameters were retrieved from the database. Post-transplant survival rates and complications, including grade III–IV complications according to the Dindo–Clavien classification, were compared between patients with an infection 1 month before transplantation and patients without an infection. Results: Eighty-four patients with an infection had statistically significant higher Model for End-stage Liver Disease (MELD), D-MELD and Balance of Risk (BAR) scores and a higher rate of acute-on-chronic liver failure compared with findings in 343 patients with no infection. The rate of infection after liver transplantation was higher in patients who had an infection before the operation: 48 per cent versus 30·6 per cent in those with no infection before transplantation ( P = 0·003). The percentage of patients with a postoperative complication (42 versus 40·5 per cent respectively; P = 0·849) and the 90-day mortality rate (8 versus 6·4 per cent; P = 0·531) was no different between the groups. Multivariable analysis showed that a BAR score greater than 18 and acute-on-chronic liver failure were independent predictors of 90-day mortality. Conclusion: Bacterial infection 1 month before liver transplantation is related to a higher rate of infection after transplantation, but does not lead to a worse outcome. Abstract : No adverse outcomes